The country estate Petersburg (Bulletin KNOB, 1996)
A ground plan of the country estate Petersburg near Nigtevegt has been preserved in the Beudeker collection (Ms. C.9.e.l1) in the British Map Library. This country estate was built by Simon Schijnvoet (1652-1727), commissioned by Christoffel Brants (1664-1732) between 1709 and 1717. The drawing is bound with an edition of De zegepralende Vecht (The triumphant river Vecht) (1719) and precedes twelve engravings of this country estate made by Daniel Stoopendaal. By means of the drawing these prints can be placed in their compositional context. In general, such prints show what used to be there, but on comparison, small differences are to be seen.The triangle gives the property a remarkable basic form. The main issue was that the site had to fit in with adjacent lots. But the triangular form with its planted avenues (illustration 1) is also to be linked up with the overgrown fortresses in Holland. Besides, fortification was a favourite subject of czar Peter the Great, for whom the construction was intended. The foundations of his town, St. Petersburg, were started with a fort.The variegation of land and water and several other details of the layout betray that the owner wished to build a 'Peter's Burg'. The layout of the garden does not show the customary symmetrical arrangement. The main axis behind the house is the visible axis but not the central one. A long traverse axis with side paths led to the various components of the garden providing an overwhelming sight and a varied walk for the guests.Schijnvoet was a capable amateur, who schooled himself with the aid of his collection of books and prints. An iconographical garden planning is not to be traced from the sculptures visible on the prints, but the many garden vases dominate. They may have been made after a design by Schijnvoet. There is a volume of 54 prints made by him, showing designs for garden decoration, including 24 examples of garden vases. The country estate Petersburg shows the significance of Schijnvoet: he was a high-level amateur and inventor mastering several 'fields of study'.